ACP 2019
DOI: 10.5709/acp-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Time Constraints in Athletes' Egocentric Mental Rotation Performance

Abstract: mental rotation sport expertise process stages egocentric transformations embodied cognition A selective effect of motor expertise on mental rotation is revealed by a high correlation between the performance of sports experts and ability on a mental rotation task. Evidence is shown by studies involving a spatial factor, such as image interference or a movement constraint. Alternatively, the time constraint, as another performance factor, is considered critical in the effect of sport expertise on mental rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Taking superiority of processing into consideration, Jansen et al (2012) took the reaction time in an un-rotation stage as an index of the perceptual stage, viz., the rotating angle is 0, and took the rotating speed as an index of rotation stage, viz., angle divided by corresponding reaction time. Jansen's viewpoints have been supported by some studies (Ozel et al, 2002;Jansen et al, 2012;Feng et al, 2019;Ke and Wang, 2021), supporting that the rotating speed is a better index over the correct rate. Neuroimaging studies on healthy populations revealed activation of specific brain regions recruited spatial cognitive processing, such as frontal (BA for Brodmann Area, BA9, BA10), premotor (BA6), parietal cortex (BA40, BA44) (Hyun and Luck, 2007).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Taking superiority of processing into consideration, Jansen et al (2012) took the reaction time in an un-rotation stage as an index of the perceptual stage, viz., the rotating angle is 0, and took the rotating speed as an index of rotation stage, viz., angle divided by corresponding reaction time. Jansen's viewpoints have been supported by some studies (Ozel et al, 2002;Jansen et al, 2012;Feng et al, 2019;Ke and Wang, 2021), supporting that the rotating speed is a better index over the correct rate. Neuroimaging studies on healthy populations revealed activation of specific brain regions recruited spatial cognitive processing, such as frontal (BA for Brodmann Area, BA9, BA10), premotor (BA6), parietal cortex (BA40, BA44) (Hyun and Luck, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Two experiments were object mental rotation (Study 1) and subject mental rotation (Study 2), using mirrored stimuli, taking reaction time (Rt) at angle 0 • as behavior index of the perceptual stage (stimulus encoding) and rotating speed as an index of the rotating stage (responsive to motor speed), taking beta of HbO change in brain areas as an index of biology. Taking the angle of rotation and reaction time into consideration, rotating speed is a sensitive index in measuring and assessing mental rotation (Ozel et al, 2002;Jansen et al, 2012;Feng et al, 2019;Ke and Wang, 2021). Based on the literature of mental rotation and depression patients, the overlapping cortex lies in frontal and motor cortex, the hypothesis 1 corresponding to the research question 1 is that, the differences of activation regions between different depressive tendencies in mental rotation could exists in frontal and motor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies found that for the poses that are possible for the human body to perform, the individual’s reaction time (RT) of mental rotation task was shorter (Amorim et al, 2006 ), proving a “spatial embodied” process. According to Wilson ( 2002 ) and previous studies of mental rotation (Feng et al, 2019 ), the embodied effect of mental rotation refers to the experience of physical activity that promotes the individual’s mental rotation and other spatial representation capabilities. In sports, the advantage of an athlete’s mental rotation is summarized as a spatial embodied effect; that is, when the space of mental rotation task matches with the physical action experience, task performance will be promoted and expert advantage will be found (Feng et al, 2017 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%